Public service motivation and career choice intentions of social work students: the roles of altruistic motivation and professional values - Hu, Zheng-Xin; Gan, Kai-Peng; Sun, Guo-Yuan; Wang, Qiu (Frontiers in Psychology, 2025)
The shortage and high turnover of social work professionals in China pose a major challenge to social governance and societal well-being, making it crucial to understand the factors influencing social work students’ career choices. Based on a purposive sampling method, between April and June 2023, a sample of 624 social work students was collected from universities in three provinces of China (Guangdong, Jiangxi, and Yunnan). The present study employs the SPSS PROCESS macro to examine the relationship between public service motivation (PSM) and career choice intentions, exploring how altruistic motivation and professional values influence the impact of PSM on career decisions. The results indicate that PSM and its dimensions strongly affect social work students’ career intentions, with altruistic motivation partially mediating this effect. Professional values positively moderate PSM’s impact, strengthening its influence on career choices. These findings provide valuable insights for social work education, guiding career strategies to reduce turnover and support the profession’s sustainable development.